Component-based modelling of a novel ductile steel connection. (1st April 2020) - Liu, Yu; Huang, Shan-Shan; Burgess, Ian
Highlights: The improved design version of a novel ductile connection has been proposed. Analytical models of the components of the novel connection have been developed. Two schemes of component-based model of the novel connection have been proposed. Component-based models have been validated against Abaqus and experiments. Examples are used to show how each spring row works during connection deformation. Abstract: To enhance the robustness of connections in fire, the improved design version of a novel ductile connection has been proposed. Performance of the improved design version of novel connection has been compared with that of the previous design version using a sub-frame model. The comparison results show that the improved version of novel connection further enhances its ductility. Five case studies have been carried out, in which the novel connections are applied to sub-frames with different beam spans. Results show that the axial forces generated in the beams with novel connections are significantly reduced compared with those of the beams with rigid connections. The analytical models for the web-cleat component of the novel connection and the WCSC component, which considers the semi-cylindrical section and the web-cleat as a whole to deform, have been developed based on simple plastic theory. Then two schemes of component-based model have been proposed for the novel ductile connection and loading and unloading behaviour have been incorporated into individual component. Result curves of the two schemes of component-based model have been compared and validated against Abaqus simulations and experiments. Finally, the proposed component-based model has been applied to two simple examples to illustrate how different spring rows work in the process of connection deformation.